NARRATIVE PARAGRAPH COMPOSITION: A DESCRIPTION OF EFL LEARNERS’ PROFICIENCY IN USING PAST TENSE - Rusmiati Rusmiati (Universitas Tanjungpura, 2022)
It is unavoidable that writing becomes a compulsory subject in English Department as it is one of notable skills that ought to be acquired by English language learners. They are demanded to possess a better writing proficiency after taking certain writing subjects. Nonetheless, writing is perceived as the most troublesome English language learning capability since it constitutes a productive skill. To specify, expressing ideas and using grammatically correct language are considered quite challenging for students. This study, accordingly, was carried out to investigate the learners’ writing production to find out their expertise in composing a past narrative paragraph in particular. Therefore, fourteen compositions of second semester students in academic year 2018/2019 were employed in this investigation. The findings show that most of them composed narrative paragraph precisely, i.e. by applying chronological development or time order. That notwithstanding, the majority of them used verb tense incorrectly in their past narrative composition.